Pengaruh Transformasi Digital, Literasi Digital dan Budaya Kerja Terhadap Kinerja Pegawai Dinas Komunikasi dan Informatika Kota Batam - Robin Ferliansyah; Sudianto Sudianto; Mulyadi Mulyadi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the impact of digital transformation, digital literacy, and work culture on employee performance at the Department of Communication and Information Technology in Batam City. In facing the digital era, the application of technology in the public sector becomes crucial for improving work efficiency and productivity. This research uses a survey method with a population of 120 employees and a sample of 55 participants. Data was collected using questionnaires and analyzed using descriptive statistics and linear regression techniques to determine the relationship between independent and dependent variables. The results show that digital transformation, digital literacy, and work culture have a significant impact on employee performance. Employees with higher levels of digital literacy and those working in a collaborative work culture exhibit better performance. The conclusion of this study is that to enhance employee performance at the Department of Communication and Information Technology in Batam City, there is a need to improve digital transformation, strengthen digital literacy, and develop a work culture that supports collaboration and innovation. This study provides recommendations for organizations to focus on digital training and cultural changes that foster a more open and productive work environment.